Molecular genotyping of measles virus strains in Perú, 2018 - Condori-Yujra, Fredy J. (2018)
Mr. Editor, in the year 2017, four countries of the Americas region reported confirmed cases of measles, namely: Argentina (3 cases), Canada (45 cases), the United States of America (120 cases) and the Republic Bolivariana de Venezuela (727 cases). In the first months of 2018, the following 9 countries have reported confirmed cases: Antigua and Barbuda (1 case), Brazil (14 cases), Canada (4 cases), Colombia (1), United States of America (13 cases), Guatemala (1 case), Mexico (4 cases), Peru (2 cases) and Venezuela (159 cases) (1).